Space-Time Fractional KdV–Burger–Kuramato Equation with Time Dependent Variable Coefficients: Lie Symmetry, Explicit Power Series Solution, Convergence Analysis and Conservation Laws - Yadav, Vikash; Gupta, Rajesh Kumar (International journal of applied and computational mathematics, 2022)
In this paper, Lie symmetry reduction, power series solutions, convergence analysis and conservation laws have been examined for the space-time fractional KdV–Burger–Kuramato equation with time dependent variable coefficients. The obtained symmetries and the Erdélyi–Kober fractional differential operator have been used to reduce the original nonlinear partial differential equation into a nonlinear ordinary differential equation. The power series solutions are also derived for the equation under consideration. Further, the obtained power series solution are examined for the convergence. The generalized Noether method has been utilized to investigate the conservation laws of the equation.